Importance-performance analysis: A comparative study of motor repair service customers - C. Boshoff (South African Journal of Business Management, 1986)
At least two American studies have found that a high percentage of new car owners do not return to the dealership they purchased their vehicle from for servicing/repairs after the initial warranty had expired. Patronage seems to have shifted to the so-called independent workshops. It appears as if the same trend prevails in South Africa and should be a source of concern to vehicle manufacturers. The study described in this article attempted to identify possible reasons for this shift in patronage and also to establish whether market requirements in general are being satisfied by these institutions. The results obtained indicate that independent workshops perform certain attributes of a motor repair service that are important to consumers markedly better than franchised dealerships do. It was further established that neither institution currently fully satisfies market requirements.
Keywords: 650